Investigations on nuclear physics with accelerated beams of polarized ions at the NSC KIPT - Slabospitsky, R.P.; Shlyakhov, N.A. (Вопросы атомной науки и техники, 2003)
The overview of polarization phenomena studies in NSC KIPT is presented.